2022
DOI: 10.7150/ijbs.67476
|View full text |Cite
|
Sign up to set email alerts
|

ENKUR expression induced by chemically synthesized cinobufotalin suppresses malignant activities of hepatocellular carcinoma by modulating β-catenin/c-Jun/MYH9/USP7/c-Myc axis

Abstract: ENKUR plays a crucial role in lung and colorectal cancers. Chemically synthesized cinobufotalin (CB) showed its significant anti-cancer effect in nasopharyngeal carcinoma. However, the roles of ENKUR and CB along with their correlation are still unknown in hepatocellular carcinoma (HCC). In this study, ENKUR expression in HCC tissue and cells were detected. The relationship between ENKUR expression and clinical pathology was also assessed. In vivo and in vitro expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Although MYH9 was originally identified as a tumor suppressive factor in squamous cell carcinoma of head and neck, 17 recent studies support a role for MYH9 as an oncoprotein in many tumors, including GC 18–23 . Interestingly, in previous studies, we have demonstrated that MYH9 interacted with ENKUR and antagonized ENKUR to induce‐cell growth and metastasis in hepatocellular carcinoma, lung adenocarcinoma, and nasopharyngeal carcinoma via suppressing p53 or elevating c‐Myc 13–15 . Nevertheless, there is no document to clarify the mechanism of ENKUR to modulate MYH9 in GC.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although MYH9 was originally identified as a tumor suppressive factor in squamous cell carcinoma of head and neck, 17 recent studies support a role for MYH9 as an oncoprotein in many tumors, including GC 18–23 . Interestingly, in previous studies, we have demonstrated that MYH9 interacted with ENKUR and antagonized ENKUR to induce‐cell growth and metastasis in hepatocellular carcinoma, lung adenocarcinoma, and nasopharyngeal carcinoma via suppressing p53 or elevating c‐Myc 13–15 . Nevertheless, there is no document to clarify the mechanism of ENKUR to modulate MYH9 in GC.…”
Section: Introductionmentioning
confidence: 90%
“… 18 , 19 , 20 , 21 , 22 , 23 Interestingly, in previous studies, we have demonstrated that MYH9 interacted with ENKUR and antagonized ENKUR to induce‐cell growth and metastasis in hepatocellular carcinoma, lung adenocarcinoma, and nasopharyngeal carcinoma via suppressing p53 or elevating c‐Myc. 13 , 14 , 15 Nevertheless, there is no document to clarify the mechanism of ENKUR to modulate MYH9 in GC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cycloheximide (CHX) chase assay and ubiquitination assay were performed as described previously [20,21]. Cells were treated with CHX (50 μg/mL) (Selleck, Shanghai, China) for Gradient time.…”
Section: Cycloheximide Chase Assay and Ubiquitination Assaymentioning
confidence: 99%
“…IFN is not toxic to the cell itself, but it inhibits the replication of a variety of viruses and possesses antitumor activity [142] . EZH2-CCF-cGAS signaling [129] MDM2/MDMX-p53 pathway [130] FBP1-DNMT1 pathway [131] NEDD4L-SMAD pathway [132] Cell cycle and EMT pathway [133] JMJD3/CLU signaling [81] p53/TfR1 pathway [134] Wnt/β-catenin signaling [39] PI3K/Akt pathway [124] Hippo pathway [107] Akt/ERK signaling [135] NF-κB signaling [136] AMPK pathway [124] Shh pathway [16] NOX4/NLRP3 pathway [137] Glucose Metabolism signaling [138] So×9-PTHrP-PTH1R axis [58] Insulin/IGF-1-like signaling [88] HIF-1α signaling pathway [139] Hedgehog signaling [140] Shoc2-ERK1/2 pathway [141] [143,144] . For example, in response to virus invasion, the body produces IFN, and the process is mediated by several factors.…”
Section: The Roles Of Usp7 In Viral Infection and Inflammationmentioning
confidence: 99%